2015
DOI: 10.1021/tx500522r
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced DNA Interstrand Cross-Linking and Direct Strand Breaks from a New Type of Binitroimidazole Analogue

Abstract: Four novel photoactivated binitroimidazole prodrugs were synthesized. These agents produced DNA interstrand cross-links (ICLs) and direct strand breaks (DSB) upon UV irradiation, whereas no or very few DNA ICLs and DSBs were observed without UV treatment. Although these four molecules (1-4) contain the same binitroimidazole moiety, they bear four different leaving groups, which resulted in their producing different yields of DNA damage. Compound 4, with nitrogen mustard as a leaving group, showed the highest I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…[5] However,t raditional DNA cross-linking agents are highly reactive species that can interact with cellular components other than DNA,t hus leadingt ou nwanted side reactions and cellular toxicity.T oimprove theselectivityand bioorthogonality of the DNA cross-linking agents, variousm ethods have been developed for inducing DNA interstrand cross-link (ICL) formation from nontoxic, or at least less toxic,c hemicals and chemical processes. [6] Some examples are fluoridei nduction, [7] H 2 O 2 , [1c, 8] NaIO 4 ,[9] and photoinduction, [10] or the use of minorgroove binding imidazole-pyrrole polyamide conjugates to improve sequence specificity for DNA alkylation. [11] Amongt hese methods, photoinduced DNA cross-linking is av ery important strategy that attracts attentionf or its biocompatibility and biological applications, because photoinductioni sanoninvasive method with high spatio-temporal resolutiona nd control, and does not require additional chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] However,t raditional DNA cross-linking agents are highly reactive species that can interact with cellular components other than DNA,t hus leadingt ou nwanted side reactions and cellular toxicity.T oimprove theselectivityand bioorthogonality of the DNA cross-linking agents, variousm ethods have been developed for inducing DNA interstrand cross-link (ICL) formation from nontoxic, or at least less toxic,c hemicals and chemical processes. [6] Some examples are fluoridei nduction, [7] H 2 O 2 , [1c, 8] NaIO 4 ,[9] and photoinduction, [10] or the use of minorgroove binding imidazole-pyrrole polyamide conjugates to improve sequence specificity for DNA alkylation. [11] Amongt hese methods, photoinduced DNA cross-linking is av ery important strategy that attracts attentionf or its biocompatibility and biological applications, because photoinductioni sanoninvasive method with high spatio-temporal resolutiona nd control, and does not require additional chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Then Li and Greenberg demonstrated that photoirradiation of the modified thymidines generated both 5‐(2′‐dexoyuridinyl)methyl radical and cation, whereas only cation intermediates directly produced DNA ICL products. Recently, Peng and co‐workers found that several bifunctional aromatic boronates cross‐linked DNA through carbocation formation upon 350 nm irradiation …”
Section: Introductionmentioning
confidence: 99%
“…Similar photoinduced C–X bond cleavage and electron-transfer processes were proposed to be involved in photochemical activation of several modified thymidines, 15,20 5-bromocytosine and 5-bromouracil, 21,33,34 as well as binitroimidazole in DNA. 35 In contrast, the trimethylamine salts ( 3b and 4b ) undergo heterolysis of the C–X bond upon 350 nm irradiation, which directly forms carbocations ( E ) that alkylate DNA complementary strands (Scheme 1b and SI, Scheme S3). Cross-linking from carbocations B or E provides a simple explanation for why efficient ICL formation was observed under aerobic conditions since the ionic intermediate ( B or E ) does not react with O 2 .…”
mentioning
confidence: 99%
“…Han et al recently described a series of binitroimidazole prodrugs that generated DNA inter-strand cross–links (ICL) and direct strand breaks (DSB) upon UV irradiation. Such DNA cross linking may lead to highly selective inhibition of DNA replication and gene expression, thereby leading to cell death [156]. Paci and co-workers designed preactivated ifosfamide (IFO), an oxazaphosphorine (alkylating agent).…”
Section: Prodrug Approach: Analog / Chemical Conjugation For Cancementioning
confidence: 99%